The Market as an Instrument of Political Control and Exploitation: Some Insights from Kenya (Nordic Journal of African Studies, 2001)
The vast majority of developing countries, especially on the African continent, have leapt into the new. The millennium is trapped in an enormous economic decline. The popular diagnosis blames the self-defeating tendencies of the Third World states as the main source of the dismal economic performance. It is against this background that the paper seeks to present an alternative account of the rampant economic stagnation experienced by developing countries on the African continent. It has been motivated by the dramatic ascendancy of Afro-pessimism, which seems to conclude that the African condition is largely of its own making and, therefore, there is little or no hope for improvement. The argument of this paper is that the colonial legacy has, to a very large extent, shaped, influenced and impacted on the range of post-colonial policy options for most countries within the policy framework of the market. The pervasive market distortions that presently characterise the majority of the economies on the continent are an enduring heritage of the colonial schemes and mechanisations.